Evaluating the relationship between pain empathy, knowledge and attitudes among nurses in North China: a cross-sectional study - Lihua Wu; Xingyu Chen; Shaofen Jia; Liya Yan; Jia Li; Liwei Zhang; Yanjing Guo; Jingjing Lu; Wanling Li (BMC, 2023)
Abstract Background Effective pain management is closely related to nurses' knowledge, attitudes and empathy regarding pain. Nursing educators and managers should understand the relationship between nurses' pain management knowledge, attitudes and empathy level, and take targeted measures accordingly. Currently, there is limited study exploring the relationship between pain empathy and pain knowledge and attitudes among nurses in North China. Objectives The purpose of this study was to investigate the level of nurses' pain management knowledge and attitudes and pain empathy, to analyze the factors influencing pain empathy, and to explore the relationship between these two variables. Design This study was a quantitative, descriptive-correlation design. Setting and participants The study population was registered nurses in North China, the sample included 177 registered nurses in North China. Methods Data were collected with the "General data questionnaire", "Knowledge and attitudes survey regarding pain" (KASRP) and the "Empathy for pain scale" (EPS) via Wechat mini program "Questionnaire Star". Results The 177 registered nurses completed the survey. The averege correct rate for KASRP was (51.94 ± 9.44)%, and none of the respondents achieved a percentage score of >80%. The mean score for pain empathy was (2.78 ± 0.78), the empathy reactions dimension was (2.99 ± 0.77), and the body and mind discomfort dimension was (2.71 ± 0.80). The results of multiple stepwise linear regression showed that whether they had received empathy training, whether they had greater trauma or severe pain and whether they had negative emotions were independent influencing factors for EPS scores. Pearson correlation analysis showed that KASRP scores were positively correlated with EPS scores (r = 0.242, P < 0.05). Conclusions The pain knowledge and attitudes of nurses in North China are far from optimal. Nurses have a relatively low accuracy rate in areas such as medication knowledge, assessment of patient pain based on case studies, and handling PRN prescriptions. Nursing educators and administrators need to design some pain management courses in a targeted manner. Nurses' empathy for pain was at a moderate level. Pain empathy was positively correlated with pain knowledge and attitudes, suggesting that empathy for pain can be developed postnatally.